Trends and key disparities of obesity among US adolescents: The NHANES from 2007 to 2020 - Deng, Yangyang; Yli-Piipari, Sami; El-Shahawy, Omar; Tamura, Kosuke (PLOS ONE, 2024)
This study aimed to estimate the trends in the body mass index (BMI) and prevalence of obesity among United States (U.S.) adolescents (10–19 years) and to examine the associations between sociodemographic factors and both BMI and obesity prevalence. The 2007–2020 National Health and Nutrition Examination Survey (NHANES), a nationally representative repeated cross-sectional survey data (n = 9,826) were used. Outcomes included: 1) Mean BMI and 2) obesity (yes/no; defined as BMI ≥95% percentile). Sociodemographic variables included age, sex, race/ethnicity, and poverty income ratio (PIR; low-income <1.3, middle-income ≥1.3 and <3.5, high-income ≥3.5). By accounting for the complex survey design, weighted generalized linear/Poisson models were used to conduct the analyses. Girls constituted 49% of the sample. From 2007–2008 to 2017–2020, there was an increase in BMI and obesity prevalence, particularly among Black and Hispanic adolescents, and those from low- and middle-income families. Additionally, there was an increase in obesity prevalence among both boys and girls. However, there were no significant changes in BMI and obesity prevalence in the other race and ethnic adolescents. Girls had a 12% (Adjusted Prevalence Ratio [APR] = 0.88; 95% CI, 0.81–0.96) lower likelihood of being obese than boys. Compared to White adolescents, Black and Hispanic adolescents had 22% (APR = 1.22; 95% CI, 1.06–1.40) and 19% (APR = 1.19; 95% CI, 1.05–1.36) greater risk of being obese. Compared to high-income families, adolescents from low- and middle-income families had 62% (APR = 1.62; 95% CI, 1.39–1.90) and 47% (APR = 1.47; 95% CI, 1.24–1.76) greater risk of being obese, respectively. The results indicated persistent disparities in obesity prevalence among different race/ethnic and sociodemographic groups. Future obesity intervention should address key disparities by targeting specific race/ethnic adolescents from low-income families and promoting health equality.